Risk factor prediction of severe postoperative acute kidney injury at stage 3 in patients with acute type A aortic dissection using thromboelastography - Guan, Xin-Liang; Li, Lei; Li, Hai-Yang; Gong, Ming; Zhang, Hong-Jia; Wang, Xiao-Long (Frontiers in Cardiovascular Medicine, 2023)
Objective Perioperative blood transfusions and postoperative drainage volume not only are the commonly recognized risk factors for acute kidney injury (AKI) but also are indirect indicators of coagulopathy in patients with acute type A aortic dissection (ATAAD). However, standard laboratory tests fail to accurately reflect and assess the overall coagulopathy profile in patients with ATAAD. Thus, this study aimed to explore the association between the hemostatic system and severe postoperative AKI (stage 3) in patients with ATAAD using thromboelastography (TEG). Methods We selected 106 consecutive patients with ATAAD who underwent emergency aortic surgery at Beijing Anzhen Hospital. All participants were categorized into the stage 3 and non-stage 3 groups. The hemostatic system was evaluated using routine laboratory tests and TEG preoperatively. We undertook univariate and multivariate stepwise logistic regression analyses to determine the potential risk factors for severe postoperative AKI (stage 3), with a special investigation on the association between hemostatic system biomarkers and severe postoperative AKI (stage 3). The receiver operating characteristic (ROC) curves were generated to assess the predictive ability of hemostatic system biomarkers for severe postoperative AKI (stage 3). Results A total of 25 (23.6%) patients developed severe postoperative AKI (stage 3), including 21 patients (19.8%) who required continuous renal replacement therapy (RRT). Multivariate logistic regression analysis demonstrated that the preoperative fibrinogen level (OR, 2.02; 95% CI, 1.03 to 3.00; p = 0.04), platelet function (MA level) (OR, 1.23; 95% CI, 1.09 to 1.39; p = 0.001), and cardiopulmonary bypass (CPB) time (OR, 1.01; 95% CI, 1.00 to 1.02; p = 0.02) were independently associated with severe postoperative AKI (stage 3). The cutoff values of preoperative fibrinogen and platelet function (MA level) for predicting severe postoperative AKI (stage 3) were determined to be 2.56 g/L and 60.7 mm in the ROC curve [area under the curve (AUC): 0.824 and 0.829; p < 0.001]. Conclusions The preoperative fibrinogen level and platelet function (measured by the MA level) were identified as potential predictive factors for developing severe postoperative AKI (stage 3) in patients with ATAAD. Thromboelastography could be considered a potentially valuable tool for real-time monitoring and rapid assessment of the hemostatic system to improve postoperative outcomes in patients.